Notes on vegetation of Guipúzcoa (Basque Country) - Loidi, Javier (Lazaroa, 1983)
In this paper nine new plants communities are described: Glycerio fluitantis-Catabrosetum aquaticae (helophytic community), Dauco gummifero-Festucetum pruinosae crithme¡osum maritimi (coastal cliff perennial grassland), Dethawio tenuifoliae-Potentilletum alehemilloidis (altimontane chasmophytic comunity), Urtico-Sambucetum ebuli angelicetosum sylvestris (nirrophilous perennial grassland), Cardao nutantis-Cirsietum richteriani (nitrophilous perennial montane íhistle comrnunity), Carici ornithopodae-Teucrietum pyrenaicae (montane calcareous comophytic grassland), Jasiono laevis-Danthonietum decumbentis (oligotrophic montane grassland), Agrosti schleicheri-Festucetum gautieri (psicro-xerophile calcarecus montane grassland), Adenocarpo-Cytisetum cantabrici (broom comrnunity) and Daboecio-Ulicetum galli vaccinietosum myrtilli (oligotrophic heathland). Nomenclatural aud syntaxonomical changes on three alredy described communities are also proposed.